2006
DOI: 10.1002/chir.20323
|View full text |Cite
|
Sign up to set email alerts
|

Separation and aquatic toxicity of enantiomers of the organophosphorus insecticide trichloronate

Abstract: Many of the organophosphorus pesticides (OPs) currently used are chiral and therefore consist of mixture of enantiomers. Despite the fact that the biological processes of chiral pesticides are enantioselective, the acute aquatic toxicity of chiral OPs with respect to enantioselectivity has so far received limited research. In this study, the enantiomeric separation and acute aquatic toxicity of trichloronate were investigated. Baseline enantioseparation of trichloronate was successfully achieved using high-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 15 publications
(13 reference statements)
2
38
0
Order By: Relevance
“…[5][6][7][8][12][13][14]32,33 In this investigation, satisfactory resolution of salithion enantiomers was achieved on all of the three CSPs of derivative cellulose and amylase we selected, among which the Chiralpak AD column offered the highest a of more than 1.20 suggesting a baseline resolution. 34 Moreover, the chiral recognition ability of Chiralpak AD also seems better than that of Chiralcel OB and Chiralpak OT(1), the two columns that have been used to separate salithion enantiomers previously.…”
Section: Results and Discussion Enantiomer Separation And Identificationmentioning
confidence: 98%
See 1 more Smart Citation
“…[5][6][7][8][12][13][14]32,33 In this investigation, satisfactory resolution of salithion enantiomers was achieved on all of the three CSPs of derivative cellulose and amylase we selected, among which the Chiralpak AD column offered the highest a of more than 1.20 suggesting a baseline resolution. 34 Moreover, the chiral recognition ability of Chiralpak AD also seems better than that of Chiralcel OB and Chiralpak OT(1), the two columns that have been used to separate salithion enantiomers previously.…”
Section: Results and Discussion Enantiomer Separation And Identificationmentioning
confidence: 98%
“…Recently, increasing studies have demonstrated that enantioselectivity also exists in the in vivo acute aquatic toxicity of chiral OPs. [5][6][7]9,10,[12][13][14] Salithion ((RS)-2-methoxy-4H-1,3,2 k 5 benzodioxaphosphorin 2-sulfide), an organophosphorus pesticide, which was first synthesized in 1963, is used for control of a broad spectrum of insect pests in orchards or vegetables. 15,16 In recent years, because of its high efficacy, low cost, and capacity to control pyrethrin-resistant pests, 17 salithion has been considered as an effective alternative of the highly toxic OPs in China.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our finding (compounds 3 and 5), the in vivo toxicities of fenamiophos, 32 leptophos, 33 and methanmidophos 11 to D. magna arose primarily from their (1)-enantiomer. In contrast, the toxicity to D. magna of the other three chiral OPs, fonofos, profenofos 4 and trichoronate, 12 was primarily from their (2)-enantiomers. The toxicities of these OPs were enantioselective.…”
Section: Enantioselectivity In Aquatic Toxicitymentioning
confidence: 78%
“…11 The acute aquatic toxicity of trichloronate to D. magna was also found to be selective that the (2)-form was 8-11 times more toxic than its (1)-form, while the racemate showed intermediate toxicity. 12 A series of 1-(substituted phenoxyacetoxy)alkylphosphonate herbicides have been synthesized. They possess notable herbicidal activities, [13][14][15][16] some of which are the inhibitors of PDHc E1.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58] Recently, enantiomeric separation and quantification of various chiral pesticides by highperformance liquid chromatography and capillary electrophoresis have been reported by various researchers. [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] The general advantages of ICP-MS detection for chiral pesticide determinations in complex environmental samples have been reported. 76) Scientists determined the S and R isomers of metolachlor (3) in water by enantioselective enzyme immunoassay.…”
Section: Chiral Separationsmentioning
confidence: 99%